HyPAM: A hybrid continuum-particle model for incompressible free-surface flows - Zhang, Qinghai; Liu, Philip L.-F. (Journal of computational physics, 2009)
Three major issues associated with numerical simulations of complex free-surface flows, viz. interface tracking, fragmentation and large physical jumps, are addressed by a new hybrid continuum-particle model (HyPAM). The new model consists of three parts: (1) the Polygonal Area Mapping method [Q. Zhang, P.L.-F. Liu, A new interface tracking method: the polygonal area mapping method, J. Comput. Phys. 227(8) (2008) 4063-4088]; (2) a new algorithm that decomposes the interested (water) phase into a continuum zone, a buffer zone and a particle zone, based on material topology and graph theory; (3) a ‘passive-response’ assumption, in which the air phase is assumed to respond passively to the continuum part of the water phase. The incompressible inviscid Euler equations and the equations describing the free fall of rigid bodies are used as the governing equations for the continuum-buffer zone and the particle zone, respectively, and separately. A number of examples, including water droplet impact, solitary wave propagation, and dam-break problems, are simulated for the illustration and validation of HyPAM. It is shown that HyPAM is more accurate and versatile than a continuum-based Volume-of-Fluid model. One major contribution of this work is the single-phase decomposition algorithm, useful for many other hybrid formulations. Neglecting surface tension, viscosity and particle interactions, HyPAM is currently limited to mildly-fragmented free-surface flows with high Reynolds and Weber numbers.